Innovation, Research and Development, and Productivity: Case Studies from Peru - Juana Kuramoto (Inter-American Development Bank (IDB), 2011)
This paper analyzes quantitative findings on the innovative behavior of firms in the production chains of pisco and shoe manufacture in Peru, which are served by the network of Technological Innovation Centers (CITEs), the most important technology policy instrument available in Peru. These two chains, in low and medium-technology industries, are representative of Perus manufacturing sector. Of particular interest is the role of technical standards as a means of technological diffusion, which is stressed in the work of the CITEs. For the pisco chain, that role involves the definition of the product itself, for which Peru is seeking a World Intellectual Property Organization (WIPO) denomination. In the shoe chain, the technical standard should act as a coordination mechanism that will help increase efficiency throughout the chain, which at present is often fractured.
Keywords: O14; O25; O33; 330